Iron Status and Helicobacter pylori Infection in Symptomatic Children: An International Multi-Centered Study - WINDLE, HENRY; KELLEHER, DERMOT P (My University, 2013)
Objective: Iron deficiency (ID) and iron deficiency anaemia (IDA) are global major public health problems, particularly in developing countries. Whilst an association between H. pylori infection and ID/IDA has been proposed in the literature, currently there is no consensus. We studied the effects of H. pylori infection on ID/IDA in a cohort of children undergoing upper gastrointestinal endoscopy for upper abdominal pain in two developing and one developed country. Methods: In total 311 children (mean age 10.7 6 3.2 years) from Latin America - Belo Horizonte/Brazil (n = 125), Santiago/ Chile (n = 105) - and London/UK (n = 81), were studied. Gastric and duodenal biopsies were obtained for evaluation of histology and H. pylori status and blood samples for parameters of ID/IDA. Results: The prevalence of H. pylori infection was 27.7% being significantly higher (p , 0.001) in Latin America (35%) than in UK (7%). Multiple linear regression models revealed H. pylori infection as a significant predictor of low ferritin and haemoglobin concentrations in children from Latin-America. A negative correlation was observed between MCV (r = 2 0.26; p = 0.01) and MCH (r = 2 0.27; p = 0.01) values and the degree of antral chronic inflammation, and between MCH and the degree of corpus chronic (r = 2 0.29, p = 0.008) and active (r = 2 0.27, p = 0.002) inflammation. Conclusions: This study demonstrates that H. pylori infection in children influences the serum ferritin and haemoglobin concentrations, markers of early depletion of iron stores and anaemia respectively
PUBLISHED
Keywords: Medicine